KEMAMPUAN PEDAGOGICAL CONTENT KNOWLEDGE MAHASISWA PENDIDIKAN BIOLOGI FKIP UMS DALAM MENYUSUN RPP TAHUN AKADEMIK 2015/2016 - PRATIWI, ATIKA INTAN; , Dra.Hariyatmi, M.Si (2016)
A teacher is one of main successful factors in learning process. Therefore, teachers must dominate some category of knowledge in order to create and do the study well, for example is Pedagogical Content Knowledge (PCK). PCK is a combination between Content Knowledge (CK) and Pedagogic Knowledge (PK) from a teacher in order to achieve the purpose of study. The purpose of this research is to know CK, PK, and PCK ability from the students of Biology Education of FKIP UMS in the preparation of lesson plan in 2015/2016 academic year. The research use documentation method. The kind of the research is qualitative descriptive. The research start from November 2015 untill April 2016 in Biology Education Studies Programe of FKIP UMS. Data of the research is CK, PK, and PCK ability from students of Biology Education of FKIP UMS in 2013 degree that havefinished Preparation of Biology Learning (PPB) subject. Populations of the research are all the data of lesson plan that have been made by 165students of Biology Education of FKIP UMS in 2013 degree. Samples are 70 lesson plan of students from class of A, B, C, D, and E that are taken by random sampling. The result of the research show that the ability of CK views of three sub aspects earn a percentage of each: a) the suitability of the material 78.22% (good), b) the breadth and depth of the material 64.04% (enough), c) material development 41.9% (approximately). PK capabilities: a) model knowledge 65.36% (enough), b) media knowledge 71.57% (good), c) evaluation knowledge 75% ( good). PCK capabilities: a) preliminary activities 65.6% (enough), b) the core activities 94.41% (excellent), and c) the closing 51.9% (approximately). Overall students get 61.39% (enough) in CK ability, 70.65% (good) in PK ability, and 70.64% (good) in PCK ability.